A Propensity Score Matching Study Between Microwave Ablation and Radiofrequency Ablation in Terms of Safety and Efficacy for Benign Thyroid Nodules Treatment - Jin, Hao; Fan, Jinrui; Lu, Ligong; Cui, Min (Frontiers in Endocrinology, 2021)
Background: Large benign thyroid nodules often lead to cosmetic problems and compression on trachea. Thermal ablation is an effective method for benign thyroid nodules treatment. Among all the thermal ablation techniques, microwave and radiofrequency are frequently used energy sources. However, treatment outcomes of the two ablation types have not been compared in detail. Therefore, we conducted this study aiming for comparing the safety and efficacy of the two ablation techniques in benign thyroid nodules treatment. Methods: Information was retrospectively collected from patients with benign thyroid nodules, who received radiofrequency ablation or microwave ablation between January 1th, 2018 and December 31th, 2019 in a main hospital in South China. Patients were divided into microwave ablation group and radiofrequency ablation group according to the techniques applied. A propensity score matching was performed to balance the baseline indexes between the two groups. We also recorded and analyzed the operative variables including operative duration, intraoperative blood loss, hospitalization time, and overall costs. Postoperative quality of life, volume reduction rates, and complication rates were routinely evaluated during the follow-up by asking patients to fulfil questionnaires at the 1st, 3rd, 6th, 12th and 18th postoperative month. Results: A total of 943 patients receiving microwave ablation or radiofrequency ablation in the years of 2018 and 2019 met our inclusion criteria. After 1:1 propensity score matching, 289 pairs of patients were matched. There was no significant difference between the two groups in operative duration, intraoperative blood loss, hospitalization time, overall cost, quality of life scores, complication rates or volume reduction rates. Conclusion: There was no significant difference between microwave and radiofrequency ablation in terms of safety and efficacy. Both of the two techniques are ideal therapeutic methods in benign thyroid nodules treatment. Registration number: ChiCTR2000034764.